(untitled) (Metallurgy and Foundry Engineering, 2010)
One of the most important issues in hot stretch-reducing process is the maintaining precision of wall thickness. Exactly the same wall thickness at all cross-sections of tubes after stretch-reducing mill increases suitability of tubes in the next treatment processes. Internal polygonization of tubes and its removal during hot reducing is constantly the most important problem. The study is a presentation of test results for decrease of internal polygonization. Internal polygonization, as a result of deformation of tube wall thickness in all stands during hot reducing, can be minimized first of all by optimization of inter-stand tension. The tubes and pipes with minimal internal polygonization could be obtained during experiments of rolling after applying maximal average tension using a developed system for equations of axial forces equilibrium in the rolling mill.